MULTIPLICATIVE ELECTROMAGNETIC-GRAVITOMAGNETIC THERMODYNAMICS OF NONEQUILIBRIUM FLEXURES OF HETEROGENEOUS COMPLEX SPACE: GRAVITOMAGNETIC PSEUDONEUTRINO IN THE LAYERED STRUCTURE OF LEPTONS, LEGIONS OF GRAVITOMAGNETIC MULTIPOLES AND RESONANCE MECHANISMS OF TURBULENCE AND GRAVITOMAGNETIC CATASTROPHES - ZASPA, YURII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Based on the analysis of collider resonance spectra and spectra of angular variations of microwave background radiation, the internal structure of charged leptons in the form of an electromagnetic nucleus and a gravitomagnetic shell with different (by sign) contributions to the total energy has been established. The rest energy of a certain particle (gravitomagnetic pseudoneutrino) associated with the electron shell has been determined: - 0.414 electron volts. The parameters of the ground and excited states of the electron shell for the first fifty components of its gravitomagnetic legion of multipoles have been calculated. The contributions of the core and shell of leptons to the total spin have been separated and it has been shown that the projection of the shell spin in excited states is not a hal-finteger, but is determined by the product of an irrational number and Planck’s constant. This nullifies the Pauli principle, which is the basis of all chemical bonds, and is the basis of disasters in the fields of nuclear energy, hydropower, controlled thermonuclear fusion, geodynamics, and the Earth’s biosphere. Existing standards in the fields of fundamental interactions (SM) and cosmology (Lambda-CDM) have been refuted. A quantitative analysis of emergency-dangerous buffeting modes of operation of technical tribosystems has been carried out, and the outdated problem of turbulence in hydro- and aerodynamics, associated with the resonant excitation of the gravitomagnetic shell of an electron, has been solved. In the work, the fine structure constant  and the elementary electric charge e are taken as the basis for calculations. The parameters c and ℏ are replaced by extended analogues that are subject to variations.